Captain underpants and the big, bad battle of the bionic booger boy Part 1: the night of the nasty nostril nuggets (New York: Scholastic, 2003)
George and Harold's latest prank has snotty school brainiac Melvin Sneedly seeing res, and he can't wait to get back at them. But when Melvin tries to transform himself into a bionic-powered superboy, things get a little gloopy-and the bionic booger boy is born!